Solving Nonlinear Fractional Differential Equations for Contractive and Weakly Compatible Mappings in Neutrosophic Metric Spaces. (21st March 2022) - Ali, Usman; Alyousef, Haifa A.; Ishtiaq, Umar; Ahmed, Khalil; Ali, Shajib
Abstract : In this article, we aim to prove various unique fixed point results for contractive and weakly compatible mappings in the sense of neutrosophic metric spaces. Several nontrivial examples are also imparted. To support main result, uniqueness of solution of nonlinear fractional differential equations is examined.